THE STATUS OF ORGANIC POLLUTION AND THEIR SPATIAL DISTRIBUTION IN THE WEST COAST OF SOUTH SULAWESI - H, A Suci Islameini; Faizal, Ahmad; Samawi, M Farid; Werorilangi, Shinta; Rasyid, Abd (Hasanuddin University, 2020)
Aquaculture activities produce organic wastes that are discharged into coastal waters and may impact the water quality. This research aimed to study the status of organic pollution and its spatial distribution on the west coast of South Sulawesi, Indonesia. Water was sampeld from two locations (Punaga Village, Takalar Regency (an open water system), and Bojo Village, Barru District (in a bay, a semi-closed water system)). Water quality was assessed by using the STORET index. Whilst to assess the spatial distribution of organic waste, an interpolation technique was used. Results showed that the water quality was categorized as highly polluted by organic pollution. The distribution of the organic pollutant, however, showed a different spatial pattern between the two locations. The difference was may be due to the different origin of the pollutant and geomorphology of the sampling locations.